Tourism Supply Chain Management: Evidence form Tourism and Hospitality Industry of Indonesia - Zaman Zaini; Taufan Maulamin; Muhammad As'ad; Mary Ismowati; Paisal Halim; Syamsiah Badruddin; Bambang Istianto (International Journal of Supply Chain Management, 2020)
The contribution of the Indonesian tourism industry in gross-domestic product (GDP) is below than other developing countries. According to the statistics, hospitality and tourism industry of Indonesia has low contribution in GDP. Therefore, this study investigated various factors which may lead to increase in contribution of this industry by increasing tourism supply chain activities. Therefore, the current study is one of the attempts to examine the role of internal and external knowledge to expediate service innovation and tourism supply chain management in Indonesia. Population of the study is based on the hospitality companies which facilitates tourists. Respondents of the study was the employees of these hospitality companies. Total 400 questionnaires were used through area cluster sampling. Partial Least Square (PLS) was used to attain final results. It is found that internal knowledge and external knowledge are the major determinants of service quality in tourism and hospitality industry. Increase in service innovation, increases the tourism supply chain. Both the internal knowledge and external knowledge has positive effect on service innovation which has positive contribution to tourism supply chain.